2008
DOI: 10.1074/jbc.m710020200
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis of Histone H3K4me3 Recognition by ING4

Abstract: The inhibitors of growth (ING) family of tumor suppressors consists of five homologous proteins involved in chromatin remodeling. They form part of different acetylation and deacetylation complexes and are thought to direct them to specific regions of the chromatin, through the recognition of H3K4me3 (trimethylated K4 in the histone 3 tail) by their conserved plant homeodomain (PHD). We have determined the crystal structure of ING4-PHD bound to H3K4me3, which reveals a tight complex stabilized by numerous inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 43 publications
2
67
0
Order By: Relevance
“…These nuclear proteins have been proposed to play roles in numerous biological functions by interacting with different acetylation and deacetylation complexes involved in chromatin remodeling and gene expression (10,11). In addition, biochemical analysis has indicated that ING4 interacts with methylated histone H3 (12)(13)(14) and with the HB01-JADE-hEAF6 histone acetyltransferase complex (11). This latter complex is responsible for most nucleosomal histone H4 acetylation in eukaryotes, and knockdown experiments indicated that Ing4-HB01 association is required for cells to progress properly through the DNA synthesis (S) phase of the cell cycle (15,16).…”
mentioning
confidence: 99%
“…These nuclear proteins have been proposed to play roles in numerous biological functions by interacting with different acetylation and deacetylation complexes involved in chromatin remodeling and gene expression (10,11). In addition, biochemical analysis has indicated that ING4 interacts with methylated histone H3 (12)(13)(14) and with the HB01-JADE-hEAF6 histone acetyltransferase complex (11). This latter complex is responsible for most nucleosomal histone H4 acetylation in eukaryotes, and knockdown experiments indicated that Ing4-HB01 association is required for cells to progress properly through the DNA synthesis (S) phase of the cell cycle (15,16).…”
mentioning
confidence: 99%
“…ING4 is a native subunit of an HBO1 histone acetyltransferase complex and contains a C-terminal conserved PHD finger that recognizes methylated histone H3 (H3K4me3) (37,38). This interaction between ING4 and H3K4me3 promotes HBO1 acetylation of H3.…”
Section: Discussionmentioning
confidence: 99%
“…Protein solutions (dialysed against PBS, pH 7.0, 2 mM TCEP) were titrated with concentrated peptide stocks prepared by dissolving the lyophilized peptides in the dialysis buffer and adjusting the pH to 7.0 with NaOH, if necessary. The binding isotherms were analysed by non-linear least-squares fitting of the experimental data to a model assuming a single set of equivalent sites 48 . Data analysis employed Microcal Origin (OriginLab) and in-house developed software.…”
Section: Methodsmentioning
confidence: 99%